A Scoping Review of Educator Proficiency Interventions in Pharmacy Education Illustrated by an Interdisciplinary Model Integrating Pedagogical Theories into Practice - Gabriella Nagy; Ferenc Arató; István G. Télessy; Aranka Varga; András Fittler (MDPI AG, 2023)
Pharmacy schools recognize the need for flexibility and comprehensive curricular transformation with a competency-based focus to effectively prepare for the evolving practitioner competencies and challenges of the pharmacy profession. The curricular implementation of evidence-based teaching and learning theories and practices demands educator proficiency through skills development with indispensable faculty leadership support. Our scoping review of online databases and pharmacy education-related journals aims to identify faculty development interventions or teaching proficiency programs that integrate educational and pedagogical theories. Original studies and reviews published between 2010 and 2022 were screened based on four inclusion criteria. Thirty-four manuscripts were eligible for full-text analysis, of which seven results referenced target faculty pedagogy knowledge development. Nine key messages, as Results Statements, synthesize and provide a framework for our results analysis. An ongoing Hungarian intervention model of comprehensive faculty development with strong interdisciplinary cooperation is discussed in our study to illustrate the applicability of the Results Statements through each stage of the process. Educator motivation and relatedness to students or awareness of the educator roles are intrinsic factors, which may not be easily detectable yet significantly impact teaching proficiency and student learning outcomes. The integration of evidence-based pedagogical knowledge and training in educator proficiency development contributes to the sustainability and cost-effectiveness of faculty interventions.